LEED building project management in Thailand - N. Chaisaard; W. Taemthong (International Association of Lowland Technology, 2018)
Green construction management practices have become a necessity in the modern construction industry. However, the ever-growing demand for green buildings in Thailand necessitates the appropriate green project management systems which are distinct from those involved in managing a conventional project. LEED certification is the most acceptable green rating system. In this research paper, seven LEED building projects in Thailand are investigated to generate information concerning the common processes inherent in green project management. Forty stakeholders, including project owners, designers, contractors, LEED consultants and facility managers associated with the projects, were interviewed. The results shown in terms of recommended management guidelines for developing LEED projects in Thailand comprising four phases. These consist of conceptual and feasibility, design, construction and project delivery phases. Our proposed guidelines can potentially benefit future green project developments in order to enhance global sustainability. This paper suggests the guideline for project management with LEED project in Thailand which is appropriate to utilize further in developing context.